Penggunaan Dan Pemenuhan Kebutuhan Pemirsa Drama Serial Sebagai Upaya Mempertahankan Tayangan Program Televisi India Di ANTV - Alysha Gardiola Fitri; Kurnia (Jayapangus Press, 2020)
Currently, private television faces the challenges of the digital broadcast industry. Even so, television stations still have the potential to survive through the industrial competition by giving shows that have an impact to the audience. In the face of competition, social adjustment and integration are very important, but another thing that must also be fulfilled is how to increase the viewers involvement. This study aims to understand the factors that affect the viewer's intentions to get involved in a television program using the theory of Uses and Gratifications approach. This study uses a quantitative approach using primary data in the form of a Likert scale. The population in this study is the audience of Indian television drama series on ANTV. According to the Nielsen ABG data in the October-December 2019, 100 respondents were determined as research samples. Data analysis was performed with Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results in this study indicate Entertainment / Relaxation (T Stat = 3,652), Social Escape & Interaction (T Stat = 2,269) Pass Time (T Stat = 2,549), and Companionship (T Stat = 3,850) proved to have a significant positive effect on Watching engagement. Research shows that Watching engagement strongly (85%) influences the independent variables. However, Information seeking was the only insignificant variable for watching engagement. This open an opportunities for a further research to explore the potential relationships and influences that can be optimized in the approach to the needs of the motives of use and fulfillment of the needs (Uses and Gratifications) of television media with studies related to Watching Engagement, especially in other television serial drama programs in similar industries.